Blended Learning as the Realization of ‘Kurikulum Darurat’ in the Pandemic of Covid 19 (Universitas Negeri Semarang, 2023)
This study aims to: (1) find out the application of the blended learning model during the COVID-19 pandemic at MI Nahdlatus Shibyan Ngemplak and MI Maslakhul Falah Glagahwaru, Undaan Kudus District; (2) find problems that arise during the implementation of the blended learning model at MI Nahdlatus Shibyan Ngemplak and MI Maslakhul Falah Glagahwaru, Undaan Kudus District. This study emphasizes more on the type of field research (field research) and is qualitative in nature, with data collection methods in the form of interviews, observation, and documentation. Based on the findings of this study, MI Nahdlatus Shibyan Ngemplak and MI Maslakhul Falah Glagahwaru used a blended learning approach to respond to mass learning during the COVID-19 pandemic. As part of the COVID-19 emergency curriculum, the concept of blended learning has been implemented in the two madrasas since the 2020–2021 school year. The blended learning model in madrasas is divided into two stages, namely planning and implementation. This program follows the syntax of the blended learning model, which includes information search, acquisition, and synthesis in online or face-to-face learning. The function of the teacher as a mediator for the ongoing teaching and learning activities cannot be separated from the successful application of the blended learning paradigm. Classroom management, management of learning activities, and learning techniques are examples of tactics that must be planned. In implementing the blended learning model, there are obstacles, including in terms of buildings and infrastructure, facilities, and parental support.